In Vivo Screening of Traditional Medicinal Plants for Neuroprotective Activity against A?42 Cytotoxicity by Using Drosophila Models of Alzheimer's Disease. - Liu, Q.F.; Lee, J.H.; Kim, Y.M.; Lee, S.; Hong, Y.K.; Hwang, S.; Oh, Y.; Lee, K.; Yun, H.S.; Lee, I.S.; Jeon, S.; Chin, Y.W.; et al. (Biological and Pharmaceutical Bulletin, 2015)
Alzheimer's disease (AD) is the most common neurodegenerative disorder, characterized by progressive neuronal loss with amyloid ?-peptide (A?) plaques. Despite several drugs currently used to treat AD, their beneficial effects on AD progress remains under debate. Here, we established a rapid in vivo screening system using Drosophila AD models to assess the neuroprotective activities of medicinal plants that have been used in traditional Chinese medicine. Among 23 medicinal plants tested, the extracts from five plants, Coriandrum sativum, Nardostachys jatamansi, Polygonum multiflorum (P. multiflorum), Rehmannia glutinosa, and Sorbus commixta (S. commixta), showed protective effects against the A?42 neurotoxicity. We further characterized the neuroprotective activity of ethanol extracts from P. multiflorum and S. commixta. A?42-expressing flies that we used showed AD neurological phenotypes, such as decreased survival and motility and increased cell death and reactive oxygen species level. However, feeding these flies extracts from P. multiflorum or S. commixta showed strong suppression of such phenotypes. Similar results were observed in human cells, so that the treatment of P. multiflorum and S. commixta extracts increased the viability of A?-treated SH-SY5Y cells. Moreover, 2,3,5,4'-tetrahydroxystilbene-2-O-?-D-glucoside, one of the main constituents of P. multiflorum, also showed similar protective activity against A?42 cytotoxicity in both Drosophila and human cells. Taken together, our results suggest that both P. multiflorum and S. commixta have therapeutic potential for the treatment of neurodegenerative diseases, such as AD.